Prensa y construcción social de la imagen de menores con medidas judiciales - Rodríguez Wangüemert, CARMEN; Torbay Betancor, Ángela; García Hernández, María Dolores; Martín Cabrera, Eduardo (Estudios sobre el Mensaje Periodístico, 2010)
The minors under judicial control and the Penal Liability of the Minors Act (5/2000) are central theme of this work, which consists of a selective analysis of 78 texts from the Canary press in recent years. The essential objective is the treatment, based on the regulatory features of journalistic praxis, of narratives decisions of writers in their role to explain and to show the chosen reality. But also, the article is a reflection on the correlation of the contents of the press, the social value of the said Act and the social perception about juvenile delinquency, since the partial results which we present belong to a multidisciplinary master project that endorsed the Consejería de Empleo y Asuntos Sociales del Gobierno de Canarias with the University of La Laguna, entitled Analysis of factors that promote resilience in minors under judicial control.
Keywords: Minor releases; Resilience; Social perception; Juvenile delinquency; Legal actions